Influence of Intrauterine Fluid Detection, Number of Transfers and Age of the Recipient on Pregnancy Rate and Early Embryonic Loss in a Commercial Embryo Transfer Program - Gian Guido Donato; Denis Necchi; Hilde Vandaele; Micaela Elizabeth Vita; Alessia Bertero; Leila Vincenti; Tiziana Nervo (Animals, 2023)
The selection of the recipient mare is one of the most important factors involved in the success of equine embryo transfer. The aim of this study was to determine whether the age of the recipient, the number of transfers and the detection of intrauterine fluid during the follicular phase or after ovulation can affect pregnancy rate at 14 and 45 days (PR 14 and PR 45) or early embryonic loss (EEL). A total of 1222 ETs were included in the study. Mares receiving the first embryo of the year had a higher PR 14 and 45 days compared to mares at the third transfer (78.8% and 70.1% vs. 65.6% and 54.1%, respectively). The detection of intrauterine fluid post ovulation negatively affected PR 14 (60.5% vs. 77.6%) and should therefore be considered an abnormal finding, probably being a sign of uterine inflammation or delayed uterine clearance. On the contrary, the age of the recipient mare and detection of fluid during follicular phase did not affect PR 14. Only the age of the recipient mare influenced the EEL, since mares aged 10–13 years had a higher EEL compared to mares aged 3–5 years (15.6% vs. 6.4%). Embryo size and grade affected PR 14 and 45.